Acid‐extractable potassium in agricultural soils: Source minerals assessed by differential and quantitative X‐ray diffraction12. Issue 3 (6th May 2013) - Andrist‐Rangel, Ylva; Simonsson, Magnus; Öborn, Ingrid; Hillier, Stephen
Abstract Different extraction methods are used world‐wide in routine soil analysis to estimate long‐term potassium (K) reserves for plants. In Sweden, K extracted with 2 M HCl at 100°C (KHCl) is frequently used, although with limited understanding of the phases extracted. In the present study, we quantified the effects of this extraction on soil minerals in particle size fractions ranging from clay to sand, and estimated their relative contribution to KHCl. The study included three Swedish long‐term agricultural field experiments with texture ranging from loamy sand to silty clay, as well as mineral specimens of K feldspar. Total weight loss of particle size fractions was determined, and quantitative and differential X‐ray powder diffraction (QXRD, DXRD), applied on solids before and after extraction, was used to quantify the dissolution of individual mineral phases. QXRD and DXRD included spray‐drying of samples, addition of an internal standard and full pattern fitting, where a combination of mineral‐standard XRD traces was matched with the experimental one. Our results show that KHCl was primarily associated with clay minerals concentrated in the two finest fractions (2–20 and < 2 μm). Highly expandable and mixed‐layer phyllosilicates were quantitatively the most important minerals dissolved. The K was released from micaceous layers in mixed‐layer phyllosilicates with a vermiculitic character. Whether di‐ or trioctahedral, a shared property of the dissolved phases was that they were rich in Fe. In the loamy sand, the coarser fractions (20–2000 μm), where feldspars were prominent, accounted for 35% of KHCl. According to DXRD, there was no significant decrease in K feldspars in any of the samples, and KHCl data for the feldspar specimens suggest that clay minerals contributed at least 70% of KHCl also in the loamy sand. Our study provides insights about the soil minerals that contribute to the long‐term K delivery capacity of soils and an explanation for the prior observation that KHCl is a dynamic fraction that can be affected by management.